Subchondral bone plate thickening precedes chondrocyte apoptosis and cartilage degradation in spontaneous animal models of osteoarthritis - Zamli, Zaitunnatakhin; Brown, Kate Robson; Tarlton, John F.; Adams, Mike A.; Torlot, Georgina E.; Cartwright, Charlie; Cook, William A.; Vassilevskaja, Kristiina; Sharif, Mohammed (Hindawi Publishing Corporation, 2014)
Osteoarthritis (OA) is the most common joint disorder characterised by bone remodelling and cartilage degradation and associated with chondrocyte apoptosis. These processes were investigated at 10, 16, 24, and 30 weeks in Dunkin Hartley (DH) and Bristol Strain 2 (BS2) guinea pigs that develop OA spontaneously. Both strains had a more pronounced chondrocyte apoptosis, cartilage degradation, and subchondral bone changes in the medial than the lateral side of the tibia, and between strains, the changes were always greater and faster in DH than BS2. In the medial side, a significant increase of chondrocyte apoptosis and cartilage degradation was observed in DH between 24 and 30 weeks of age preceded by a progressive thickening and stiffening of subchondral bone plate (Sbp). The Sbp thickness consistently increased over the 30-week study period but the bone mineral density (BMD) of the Sbp gradually decreased after 16 weeks. The absence of these changes in the medial side of BS2 may indicate that the Sbp of DH was undergoing remodelling. Chondrocyte apoptosis was largely confined to the deep zone of articular cartilage and correlated with thickness of the subchondral bone plate suggesting that cartilage degradation and chondrocyte apoptosis may be a consequence of continuous bone remodelling during the development of OA in these animal models of OA.